Validation of heart failure quality of life tool and usage to predict all-cause mortality in acute heart failure in Uganda: the Mbarara heart failure registry (MAHFER) - Okello, Samson; Abeya, Fardous Charles; Lumori, Boniface Amanee Elias; Akello, Suzan Joan; Moore, Christopher Charles; Annex, Brian H.; Buda, Andrew J. (BMC cardiovascular disorders, 2018)
Background: The health-related quality of life (HRQoL) is an important treatment goal that could serve as low-cost prognostication tool in resource poor settings. We sought to validate the Kansas City Cardiomyopathy Questionnaire (KCCQ) and evaluate its use as a predictor of 3 months’ all-cause mortality among heart failure participants in rural Uganda. Methods: The Mbarara Heart Failure Registry Cohort study observes heart failure patients during hospital stay and in the community in rural Uganda. Participants completed health failure evaluations and HRQoL questionnaires at enrollment, 1 and 3 months of follow-up. We used Cronbach’s alpha coefficients to define internal consistency, intraclass correlation coefficients as a reliability coefficient, and Cox proportional hazard models to predict the risk of 3 months’ all-cause mortality. Results: Among the 195 participants who completed HRQoL questionnaires, the mean age was 52 (standard deviation (SD) 21.4) years, 68% were women and 29% reported history of hypertension. The KCCQ had excellent internal consistency (87% Cronbach alpha) but poor reliability. Independent predictors of all-cause mortality within 3 months included: worse overall KCCQ score (Adjusted Hazard ratio (AHR) 2.9, 95% confidence interval (CI) 1.1, 8.1), highest asset ownership (AHR 3.6, 95% CI 1.2, 10.8), alcoholic drinks per sitting (AHR per 1 drink 1.4, 95% CI 1.0, 1.9), New York Heart Association (NYHA) functional class IV heart failure (AHR 2.6, 95% CI 1.3, 5.4), estimated glomerular filtration rate (eGFR) 30 to 59 ml/min/1.73m2 (AHR 3.4, 95% CI 1.1, 10.8), and eGFR less than 15 ml/min/1.73 m2 (AHR 2.7, 95% CI 1.0, 7.1), each 1 pg/mL increase in Brain Natriuretic Peptide (BNP) (AHR, 1.0, 95% CI 1.0, 1.0), and each 1 ng/mL increase in Creatine-Kinase MB isomer (CKMB) (AHR 1.0, 95% CI 1.0, 1.1). Conclusion: The KCCQ showed excellent internal consistency. Worse overall KCCQ score, highest asset ownership, increasing alcoholic drink per sitting, NYHA class IV, decreased estimated glomerular filtration rate, BNP, and CKMB predicted all-cause mortality at 3 months. The KCCQ could be an additional low-cost tool to aid in the prognostication of acute heart failure patients.
Keywords: Acute heart failure; All-cause mortality; Kansas City cardiomyopathy questionnaire; 36-item short form health survey; Sub-Saharan Africa